Alloy design strategy for microstructural-tailored scandium-modified aluminium alloys for additive manufacturing. (15th January 2022) - Schimbäck, D.; Mair, P.; Bärtl, M.; Palm, F.; Leichtfried, G.; Mayer, S.; Uggowitzer, P.J.; Pogatscher, S.
Abstract: To exploit the full potential of the additive layer manufacturing technique it is necessary to adapt the material to the process via a smart alloy design strategy. To this end, in order to derive and investigate various material concepts, the microstructural evolution of Sc-modified Al alloys was studied during the course of their production by laser powder bed fusion. Adding Mg as the main element (Al-4.4Mg-0.8Sc-0.3Zr-0.5Mn) generates an already-familiar bimodal microstructure. In contrast, if Cr is added as the main element (Al-2.6Cr-0.7Sc-0.3Zr), epitaxial grain growth takes place across several weld tracks, resulting in a distinct texture; and adding Ti as the main element (Al-1Ti-1Sc-0.4Zr) produces a uniform ultrafine-grained microstructure. The differences between these microstructures arise from interactions of the grain growth restriction factors and the solute with the primary precipitation structure. Thus, the precise manipulation of key metallurgical factors leads to novel materials which can be tailor-made for certain requirements. Graphical abstract: Image, graphical abstract